THE ACTORS OF A WIND POWER CLUSTER: A CASE OF A WIND POWER CAPITAL - Jari M. Sarja (Journal of Urban and Environmental Engineering, 2013)
Raahe is a medium-sized Finnish town on the western coast of Northern Finland. It has declared itself to become the wind power capital of Finland. The aim of this paper is to find out what being a wind power capital can mean in practice and how it can advance the local industrial business. First, the theoretical framework of this systematic review study was formed by searching theoretical information about the forms of industrial clusters, and it was then examined what kinds of actors take part in these types of clusters. Finally, the actors of the case area were studied. The core companies of wind power clusters are the wind turbine manufacturers, component manufacturers, developers of the wind farms, wind power operators, and service and maintenance organizations. Understanding of the wind power cluster structure may help decision makers to develop the best possible conditions for the emergence of clusters.